Analysis Of Mathematical Problem Solving Ability Of Two Variable Linear Equation System Material In Terms Of Learning Style - Arjudin; Nurvitasari, Try; Kurniawan, Eka; Subarinah, Sri (Balai Publikasi Indonesia, 2024)
This study aims to describe the problem-solving ability of two-variable linear equation system material in students with visual, auditorial, and kinesthetic learning styles. This type of research is descriptive qualitative. The subjects of the study were grade VIIIB students of SMPN 1 Gunungsari for the 2023/2024 school year, totaling 20 students, with 5 students of visual learning style, 7 students of auditorial learning style, and 8 students of kinesthetic learning style. The sampling technique is carried out by purposive sampling technique. The research instruments are questionnaires, test questions, and interviews. The data analysis technique used is data reduction, data presentation, and conclusions. Analysis is carried out based on John Dewey's stages, namely facing problems, defining problems, finding solutions, testing several solutions, and choosing the best hypothesis. Based on the results of the study, it was obtained that, students of visual learning style, in general, have high problem-solving skills because they are able to carry out all five stages. Students of auditorial learning style, in general, have high problem-solving skills, where auditorial students are able to carry out all five stages. Meanwhile, the kinesthetic learning style has moderate problem-solving abilities, where kinesthetic students are only able to carry out four stages, because at the stage of choosing the best hypothesis, kinesthetic students are not able to carry it out